Chloe Cecil: capstone - Cecil, Chloe, artist (Colorado State University. Libraries, 2022)
The artist's statement: My journey as a potter began when I took my first ceramics class in my undergraduate studies at Colorado State University. An assignment that was based on recreating historical forms pulled me into the world of pottery and helped me to develop a relationship with clay and tradition that reinvigorated my love of making. In conjunction with a BFA in ceramics, I have also pursued a BA in Art History. The knowledge I have gained through my art history education has expanded my overall historical art knowledge and vocabulary while also teaching me concrete research skills that I actively use in my studio practice. For my capstone exhibition, I have created a collection of pots inspired by historical pot forms from several different cultures and time periods such as a 15th century pot from Korea and a 13th century pot from Iran. I started the process by first sketching pots from ceramic books and then selecting five forms that would push my technical skills. I decided to remake each piece with the same proportions and forming processes as the original historical pot but at a larger scale. While creating these five historical forms, I took the knowledge I was gaining from them to create ten smaller vessels inspired by the original five pots. The surface designs on each piece are from my own imagination. In this body of work, I explored carving techniques and black and white slip to create a common thread throughout the vessels. With this body of work my hope is to bring history back to the present and remind my viewer that history is still relevant to our lives today and is not solely in the past. This is particularly relevant to the ceramics field as so much of what we do in ceramics is based on long standing techniques and traditions. I am also striving to create personal relationships with the original makers of these pots by visiting their work in the present and being led by their hands in some way. Through the making of these pieces I am developing more gratitude for the makers that came before me, as all artists stand of the shoulders of their predecessors.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: pottery